RANCANG BANGUN SISTEM MOBILE NOTIFICATION CHAT DENGAN SOCKET SERVER BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract - The notification is a notification in the form of services such as voice, a twinkle LED lights and icon on the main screen smartphone that indicates that there is a new incoming message. This notification service is common in applications mobile messenger application and email service. Number of providers and users of instant messaging services to make the reduced function of the application, such as, the number of ads that appear and frequent occurrence of delays in the delivery of the message (pending) that interfere with the smooth running of users in communicating. This research will make mobile notification system android based chat using the programming socket is private server, that can be used to help users in an organization to conduct communications with ease without any interruption or delay in the send and receive messages from other users. Mobile system notification this chat is created by using the Java programming language with the help of eclipse and the android SDK. As for the databases used are MySql and PHPMyAdmin using the PHP programming language to connect to the database by the system. This research resulted in mobile chat system can be used to send and receive text messages, and equipped with a Notification Services icon on the main screen, if there is a request for a new friendship or a new message that is sent by another user. Of the test is done, the system is running in accordance with the purpose of making the system. Keywords: Mobile, Instant Messaging, Notification, Socket Programming Abstrak - Notifikasi adalah suatu layanan dalam bentuk pemberitahuan seperti suara, kedipan lampu LED dan icon pada layar utama smartphone yang menandakan bahwa ada pesan baru yang masuk. Layanan notifikasi ini biasa terdapat pada aplikasi – aplikasi mobile messenger dan email service. Banyaknya penyedia dan pengguna layanan instant messaging membuat berkurangnya fungsi dari aplikasi tersebut seperti, banyaknya iklan yang muncul dan sering terjadinya keterlambatan dalam pengiriman pesan (pending) yang mengganggu kelancaran pengguna dalam berkomunikasi. Penelitian ini akan membuat sistem mobile notification chat berbasis android dengan menggunakan pemrograman socket yang bersifat private server, agar bisa digunakan untuk membantu pengguna di suatu organisasi dalam melakukan komunikasi dengan nyaman tanpa adanya gangguan atau keterlambatan dalam mengirim dan menerima pesan dari pengguna lain. Sistem mobile notification chat ini dibuat dengan menggunakan bahasa pemrograman Java dengan bantuan eclipse dan SDK android. Sedangkan untuk database yang digunakan adalah MySql dan PHPMyAdmin dengan menggunakan bahasa pemrograman PHP untuk mengkoneksikan database dengan sistem. Penelitian ini menghasilkan sistem mobile chat dapat digunakan untuk mengirim dan menerima pesan teks, serta dilengkapi dengan layanan notifikasi berupa icon pada layar utama, apabila terdapat permintaan pertemanan baru atau pesan baru yang dikirimkan oleh pengguna lain. Dari uji coba yang dilakukan, sistem berjalan sesuai dengan tujuan pembuatan sistem. Kata Kunci : Mobile, Instant Messaging, Notification, Socket Programming